DEVELOPMENT OF RICE VARIETIES ON SALINE SOILS - Komilov Sh.; Kadirov B.; Bozorboyev N.; Ruzimov B. (Web of Journals Publishing, 2024)
This article discusses the development of rice varieties on saline soils.
Keywords: rice, variety, salt, soil, import, development.